Still Fighting for Breath: a patient survey of the challenges and impact of severe asthma. Issue 4 (21st December 2018) - Katsaounou, Paraskevi; Odemyr, Mikaela; Spranger, Otto; Hyland, Michael E.; Kroegel, Claus; Conde, Lorena Garcia; Gore, Robin; Menzella, Francesco; Domingo Ribas, Christian; Morais-Almeida, Mario; Gasser, Matthias; Kasujee, Ismail
We conducted a large global survey, Still Fighting for Breath, in patients with severe persistent asthma, 10 years after the Fighting for Breath survey to assess the impact of disease on patients' lives and to determine if control and management have changed in recent years. Data were collected from 1333 adults (aged >18 years) and caregivers of children (aged 6–17 years) with severe persistent asthma from nine countries through an online survey conducted in 2016 by GfK. A decade after the first survey, our results showed that the impact of severe asthma has not changed significantly and a high proportion of patients with severe asthma remain inadequately controlled. A large discrepancy was observed between the proportion of patients who perceived their asthma to be well controlled (42%) and the proportion of patients who reported to be well controlled as per the Global Initiative for Asthma (GINA) assessment (6%). Although most patients perceived their asthma to be controlled, many experienced frequent symptoms that affected their daily lives. Thus, there is a need for improved management (support and strategies) of patients with severe persistent asthma and improved coordination of efforts that would enable these patients to achieve better disease control. There is a need for improved management of patients with severe persistent asthma to achieve better disease control http://ow.ly/rv5K30mQdGG